2022
DOI: 10.25105/jet.v2i1.13561
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Inflation and Exchange Rate on Exports in 5-Year Asean Countries (Years 2010–2020)

Abstract: International trade is a form of economic cooperation between two or more countries that provides direct benefits. International trade has an important role because a country cannot meet all domestic needs and with international trade, every country in the world can exchange resources owned by each country, with the aim that there is no excess or lack of resources in each country in the world. This research was conducted in 5 countries in ASEAN, namely Indonesia, Singapore, Thailand, Malaysia, and the Philippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The study also revealed that the Rupiah exchange rate has a substantial impact on inflation. Conversely, research by Ilmas et al (2022) found that exchange rates have a negative and significant effect on exports in five ASEAN countries. This suggests that if the exchange rate in a country increases, exports will decrease, and vice versa.…”
Section: Effect Of Exchange Rate On Inflationmentioning
confidence: 89%
“…The study also revealed that the Rupiah exchange rate has a substantial impact on inflation. Conversely, research by Ilmas et al (2022) found that exchange rates have a negative and significant effect on exports in five ASEAN countries. This suggests that if the exchange rate in a country increases, exports will decrease, and vice versa.…”
Section: Effect Of Exchange Rate On Inflationmentioning
confidence: 89%
“…A negative inflation variable indicates that increasing inflation reduces economic growth. This indicates that higher inflation rates can decrease people's purchasing power as the prices for products and services rise [13]. This can reduce people's capacity and ability in production and consumption activities, which has implications for decreasing economic growth.…”
Section: Determinants Of Credit Rice Production and Economic Growth I...mentioning
confidence: 99%
“…Sumatera Utara, Roberto Anggiat Iron Lumban Gaol dan I Wayan Sukadana pada pasar dunia melalu kegiatan ekspor (Safitri, 2015). Ilmas et al (2022) berpendapat bahwa kinerja ekspor yang kuat sebagai salah satu faktor penting dalam mendorong pertumbuhan ekonomi.…”
Section: Elastisitas Ekspor Sektor Pertanian Terhadap Ipm Ketimpangan...unclassified